Oil Price and Leverage for Mining Sector Companies in Indonesia - Endri, Endri; Supeni, M. Iqbal Rasyid; Budiasih, Yanti; Siahaan, Matdio; Razak, A.; Sudjono, Sudjono (International Journal of Energy Economics and Policy, 2021)
The research was conducted to prove empirically the impact of oil prices, interest rates, profitability, company size, and liquidity on leverage in mining sector companies in Indonesia. The study population was 47 companies in the mining sector, using the purposive sampling method, the research sample was selected as many as 32 companies in a period of 5 years from 2014 to 2018 so that 160 observations were obtained. The data analysis method used a random-effects model selected from panel data regression. The empirical findings show that profitability, liquidity, world oil prices, and interest rates have a negative effect on leverage, while firm size has no impact. The empirical findings of this study can help the mining sector industry in Indonesia in making decisions about corporate debt policies that are significantly influenced by oil prices, profitability, liquidity, and interest rates to create optimal debt policies. Keywords: Oil Price, Leverage, Mining Sector Companies, Indonesia JEL Classifications: G22, E22, E44, Q43 DOI: https://doi.org/10.32479/ijeep.11237